Monthly fuel usage (of the main engines, generator sets and boilers) of ships travelling to Australian Antarctic Stations - AADC (owner); AADC, DATA OFFICER (distributor); AADC, DATA OFFICER (custodian); AU/AADC > Australian Antarctic Data Centre, Australia (hasAssociationWith); Australian Antarctic Data Centre (publisher); Australian Antarctic Division (sponsor); BRYSON, ROB (collaborator); BRYSON, ROB (hasPrincipalInvestigator); Bryson, R. (originator); CONNELL, DAVE J. (author)
Progress Code: completed Statement: This indicator is now OBSOLETE. These data are no longer archived in this location, and are therefore not up-to-date. Changes in the quantity of fuel used provide an indication of efficiencies in the plant, energy saving strategies and/or an indication of sea ice the vessel is encountering. The fuel usage by the vessels main engines and generators provides an indication of the energy requirements of the vessel. This is proportional to the sea and ice conditions encountered, but also provides an indication of the ongoing efficiency of the vessels over a given time. Accuracy of figures Figures used should not be relied on for accuracy of more than +/- 2 tonne due to the method used for testing usage. Fuel The accuracy of recording ships fuel figures each day has traditionally been quite poor. Total fuel consumption is based on the number of running hours multiplied by the nominal fuel consumption of the engine. Dips of the tanks are conducted when conditions allow. A correction is then applied to the figure for fuel remaining on the vessel. This process means that a correction may be applied to one month's consumption, but be indicative of three months usage, one month may be out by the error accumulated over three months. The value of this correction can normally be expected to be in the vicinity of 10,000 litres. For the last three years the Aurora has had a fuel flow meter fitted to the main engines. Therefore figures for fuel usage for the last three years could be considered more accurate than the proceeding years. Days Steaming The recording of the number of days steaming is the most problematic of any of the figures. The number of days steaming has been taken as any day that the vessel is at sea. That is, when the vessel is not at a station or in an Australian port. Problems associated with this method are highlighted by marine science voyages. For example, the vessel may be at sea for the entire month, but due to the use of the CTD or trawling, the engines are not ...